Composition And Characteristic Of The Surficial Sediments In The Southern Corniche Of Jeddah, Red Sea Coast - Al-Dubai, Talha A; Antoni, Satria; Al-Zubieri, Aaid G; Majeed, Jawad (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
This work discusses the composition and characteristic of the surficial sediments in the southern corniche of Jeddah, Saudi Red Sea coast, in an attempt to infer the surficial distribution pattern of minerals and provenance of sediments. Twenty-six superficial sediments samples were collected from backreef and forereef areas and were analyzed for grain size, CaCO3 content, and mineralogy. The textural of grain size range from gravel to mud fraction. The mud-dominated substrates (<63 Âµm) occur generally in the back-reef area near the shoreline (sheltered area) and in the lagoon. Gravel rich-sediments are mostly found in forereef regions. The highest content of aragonite and Mg-calcite occur in the forereef area, probably because to suitability the forereef region for chemical and biochemical precipitation of these minerals. High Mg-calcite and Dolomite are low in both the regions. The pyrite occurs in lagoon; this indicates the reductive conditions in this part. However, on the contrary the percentage of carbonate minerals were low in the backreef-flat area, which could be attributed to the supply of non-carbonate terrigenous materials. The terrigenous material contains quartz, k-feldspar, plagioclase and amphibole minerals and are dominant in backreef-flat area with averages of 12.7%, 7.13%, 2.93% and 0.65%, respectively. Their abundance could be attributed to the supply of terrigenous materials by Aeolian deposits and intermittent Wadis.